Pengembangan Potensi Desa Wisata (Studi Kasus Desa Wisata Sugih Waras di Kabupaten Ogan Komering Ilir, Palembang) - Mustika Permatasari; Enos Julvirta; M. Rian Ahdian Morena (STIEPAR YAPARI Bandung, 2022)
South Sumatra is one of the travel destinations for visitors to visit, one of the attractions of tourism found in south Sumatra is Rumah Limas Seratus Tiang. The purpose of research is to identify potential tourism in the village of Sugih Waras and to plot a strategic move in the development of the tour village Sugih Waras. Data collection is done through in-depth interviews, document study and observation. Qualitative data analysis of the potential for Tours in the village of Sugih Waras, village support in the development of Tours in the village Sugih Waras and strategic plans in the development of the tourist village Sugih Waras. Research shows the potential for tourism to be developed in the village of Sugih Waras, a natural tourist potential, the Komering River lying across the street from the Rumah Seratus Tiang, a hundred yards away, and the cultural potential of the Rumah Limas Seratus Tiang and the tomb of Prince Redjed Wiralaksana, which lies directly behind Rumah Limas Seratus Tiang. The strategic plan for the development of the Rumah Limas Seratus Tiang, among other things: in its next generation of grants aimed at building an attraction of Desa Wisata Sugih Waras panoramic view. As for other strategic attractions development plans by holding regional dance races, distich and song competitions; Accessibility development by road improvement, transportation to tourist villages; The amenity with the provision of the sound system, the costume of the dancer and the development of the attraction by making securing village Sugih Waras one of history's destines equipped with the activities of the distich and the singing of the region. This is being done to realize the potential development of a village tour potential in Desa Sugih Waras.